Reconstruction of a Spinal Accessory Nerve Defect Using Vascularized Vastus Lateralis Motor Nerve Graft - Shiori Yanagishita, MD; Naoya Otani, MD; Shien Seike, MD; Koichi Tomita, MD, PhD; Tateki Kubo, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2023)
Summary:. Massive resection of a malignant tumor of the head and neck region often requires loss of critical nerves, including the spinal accessory nerve. Recently, vascularized nerve grafts (VNGs) have been used to repair facial and other nerve defects with successful outcomes, even in cases involving factors that can inhibit nerve regeneration, such as radiotherapy. However, the effectiveness of these nerve grafts against postoperative radiotherapy has yet to be explored. We report the first successful case in reconstructing a spinal accessory nerve defect after total left parotidectomy with radical neck dissection, using a vascularized vastus lateralis motor nerve graft and an anterolateral thigh flap based on the lateral circumflex femoral system, with great shoulder function outcomes even after postoperative radiotherapy. A branch of vastus lateralis motor nerve perfused by the accompanying descending branch of lateral femoral circumflex vessel was used as a nerve graft, and was repaired in an end-to-end manner. The patient underwent postoperative radiotherapy to the area of operation. At 6-months follow-up, the patient was capable of 90 degrees lateral shoulder abduction, and at 18 months, achieved full-range shoulder abduction and reported neither functional limitations of the shoulder nor complaints of any shoulder pain (Disabilities of Arm, Shoulder, and Hand score 0). Although further study is necessary to fully understand the superiority of VNGs over postoperative radiotherapy, immediate nerve reconstruction using VNG for accessory nerve defects in patients scheduled for radiotherapy postoperation may be extremely beneficial for preserving shoulder motor function and sustaining the patient’s quality of life.